Applying a Deep Learning Instructional Approach in Rhythmic Gymnastics Learning for Phase D Grade VIII Junior High School Students - Boangmanalu, Perolihen Natalia; Siregar, Samsuddin; Napitupulu, Ester Febriyanti; Manurung, Valentia Febriyani; Subakti, Falih Ariq; Togatorop, Mardongan; Wibowo, Sarwoedi; Tarigan, Enzi Yoel Fransiskus; Manalu, Muhammad Fadli Boang (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the Study: This study aims to determine the effectiveness of rhythmic gymnastics learning using a deep-learning approach among Phase D eighth-grade students at SMP Negeri 13 Medan. The deep-learning approach was applied to foster deeper conceptual understanding through movement analysis, reflective discussion, and gradual practice. Materials and Methods: The study employed a descriptive qualitative method. Data were collected through classroom observations, documentation of learning activities, and field notes, which were then analyzed through data reduction, data display, and conclusion drawing. Results: The findings indicate that the deep-learning approach effectively enhances students’ understanding of rhythm, tempo, and movement patterns. Psychomotor skills—including coordination, flexibility, and accuracy in following rhythms—showed noticeable improvement. Additionally, students demonstrated increased engagement, confidence, and motivation throughout the learning process. They were also able to independently analyze movement errors and collaborate in creating rhythmic gymnastics sequences. Conclusions: Rhythmic gymnastics learning based on a deep-learning approach provides a meaningful and effective learning experience for junior high school students. It strengthens conceptual comprehension, improves psychomotor proficiency, and cultivates active participation and reflective learning, thereby enhancing the overall quality of Physical Education instruction.